2016
DOI: 10.3389/fpsyg.2016.01799
|View full text |Cite
|
Sign up to set email alerts
|

Grit or Honesty-Humility? New Insights into the Moderating Role of Personality between the Health Impairment Process and Counterproductive Work Behavior

Abstract: It is acknowledged that chronic job demands may be depleting workers’ stamina resulting in burnout conditions and ultimately causing further health problems. This relation, known as health impairment process, has recently been considered as a possible explanation for the emergence of counterproductive work behavior (CWB). The present work aims to examine the role of two personality traits (i.e., Grit and Honesty-Humility) in this process. The results, based on a sample of 208 private service sector employees, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 76 publications
5
51
0
Order By: Relevance
“…For example, from the standpoint of equity and justice theories, the study of Aquino et al (1999) confirmed that interactional justice had a negative effect on CWB-O and that distributive and interactional justice had effects on CWB-I. In addition, examining the health impairment process in relation to the Job Demand-Resources (JD-R) model framework, Ceschi et al (2016) found that the relationship between job demands and CWB was not only mediated by burnout but also moderated by personality traits (i.e., grit and honesty-humility). From a social exchange perspective, Colbert et al (2004) found that the perception of a supportive work environment was negatively related to CWB.…”
Section: Introductionmentioning
confidence: 84%
“…For example, from the standpoint of equity and justice theories, the study of Aquino et al (1999) confirmed that interactional justice had a negative effect on CWB-O and that distributive and interactional justice had effects on CWB-I. In addition, examining the health impairment process in relation to the Job Demand-Resources (JD-R) model framework, Ceschi et al (2016) found that the relationship between job demands and CWB was not only mediated by burnout but also moderated by personality traits (i.e., grit and honesty-humility). From a social exchange perspective, Colbert et al (2004) found that the perception of a supportive work environment was negatively related to CWB.…”
Section: Introductionmentioning
confidence: 84%
“…Importantly, Schaufeli's notion of work engagement may be located in the well-established theoretical framework of the Job Demands-Resources theory (JD-R), a model which attempts to predict work engagement using two broad sets of conditions: job demands and job resources Bakker and Demerouti 2014;Demerouti and Bakker 2011). Job demands trigger stress, consume an employee's energy, generate strain, impact employee's health, and eventually lead to burnout (Ceschi et al 2016;Maslach et al 2001). Conversely, job resources trigger motivational processes, act as an Benergy reservoir^, and are a positive force, facilitating the successful completion of work tasks and decreasing the psycho-physiological costs of job demands, while also helping to fulfill psychological needs.…”
Section: Why Work Engagement May Be Importantmentioning
confidence: 99%
“…While it would be difficult to gather an objective measure on these behaviors, further research comparing director, peer, and self-ratings, especially using a larger sample, would be interesting. It would also be interesting to explore these relationships using more complex methods of collecting and analyzing personality data (e.g., Sartori et al, 2017) or potentially incorporating other personality indicators such as grit, honesty, and humility into the understanding of behaviors displayed during leader development (Ceschi et al, 2016). …”
Section: Discussionmentioning
confidence: 99%